Growth through research and development - Heike Belitz; Simon Junker; Max Podstawski; Alexander Schiersch (DIW Economic Bulletin, 2015)
DIW Berlin has examined the effects of investment in research and development on economic growth in Germany and other OECD countries. Their results show that an increase of one percentage point in research and development spending in the economy as a whole leads to a short-term average increase in GDP growth of approximately 0.05 to 0.15 percentage points. The coefficient for Germany is at the upper end of that range. The analysis shows, however, that it is difficult to separate the effect of aggregate R&D into contributions from private- and public sector R&D. R&D investment in both sectors has seen strong growth in Germany in recent years, particularly when compared internationally. For a country that owes its prosperity largely to its research-intensive manufacturing sector and to production-related, knowledge-intensive services, research and development remains key to future growth. It is therefore essential that Germany does not ease up on its efforts to increase R&D investment.
Keywords: O11; O30; O47; C33; 330; Economic growth; Research and Development; International comparison